If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(x-6)=-(x+2)
We move all terms to the left:
7(x-6)-(-(x+2))=0
We multiply parentheses
7x-(-(x+2))-42=0
We calculate terms in parentheses: -(-(x+2)), so:We get rid of parentheses
-(x+2)
We get rid of parentheses
-x-2
We add all the numbers together, and all the variables
-1x-2
Back to the equation:
-(-1x-2)
7x+1x+2-42=0
We add all the numbers together, and all the variables
8x-40=0
We move all terms containing x to the left, all other terms to the right
8x=40
x=40/8
x=5
| 40x-30=19 | | 9(y+1)=-5y-33 | | -5(3-k)=15 | | 9+3|4x+3|=19 | | 4x^2+14x=1000 | | 27-5x=-18 | | 2x-5.75=-4.11 | | 3x^2+15x=528 | | 9x-5.06=0.07 | | 2x+5=−3x+15 | | 4.905t^2-6t+4=0 | | 9-8x-7-13x=5 | | 5+x-4=3 | | 9-10x-6-5x=6 | | 3(u-7)-5u=-31 | | 1.2x=4.8/2 | | 10x-6+7x+11=90 | | 3(x+2)=8x-4 | | 5(3x+9)=-48+3 | | 15=-42n | | 4y−6=−2(−2y−1) | | 5/8x-1/2=1/5 | | 3x+6=2(x-1) | | -8m-28=-7(m+5) | | 4y+1=6y-20 | | 3x+15=3(x | | 3/5d-1/7=1/2 | | 2(7s+6)-5s=3(3s+6)+20 | | 6/7y-9=3 | | x=1.80(x)+32 | | 9x-x=-3+2x-2-1 | | x×2+7x+10=0 |